Wettability changes in polyether impression materials subjected to immersion disinfection - Shweta Shetty; Giridhar Kamat; Rajesh Shetty (Wolters Kluwer Medknow Publications, 2013)
Background: Disinfection of impression materials prevents cross-contamination; however, the disinfectants may alter the wettability property. The purpose of this investigation was to evaluate the wettability changes of polyether impression material after immersing in four different chemical disinfectant solutions for a period of 10 min and 30 min, respectively. Materials and Methods: A total of 45 samples of polyether dental impression material (Impregum soft, 3MESPE, St. Paul, MN, USA) were randomly divided into nine groups with five specimens each. Each specimen was disc shaped, flat of 32 mm diameter and 3 mm thickness. The samples were immersed in four disinfectant solutions: 2% Glutaraldehyde, 5% sodium hypochlorite, 0.05% iodophor, and 5.25% phenol for 10 min and 30 min, respectively. The control was without disinfection. Wettability of the samples was assessed by measuring the contact angle by using the Telescopic Goniometer. Data were subjected to analysis of variance (Fisher's test) and Tukey's post hoc test for multiple comparisons at 5% level of significance. Results: The contact angle of 20.21° ± 0.22° were recorded in the control samples. After 10 min, the samples that were immersed in 5% sodium hypochlorite and 5.25% phenol showed significant statistical increase in the contact angle as compared to the control (P < 0.001). After 30 min of disinfection, only the samples immersed in 0.05% iodophor showed there were no significant changes in the contact angle, whereas the other disinfectants significantly increased the contact angle and decreased the wettability of the polyether material. Conclusion: Within the limitations of the study, 2% glutaraldehyde proved safe for 10 min of immersion disinfection while 0.05% iodophor holds promise as an effective disinfectant without affecting the wettability of the material.